In celebration of the 60th birthday of 2 microfluidics pioneers: Professor Susan Lunte and Professor James Landers. Issue 28 (3rd July 2018) - Easley, Christopher J.; Regan, Fiona; Roper, Michael G.; Martin, R. Scott
Abstract : Christopher Easley, Fiona Regan, Michael Roper and R. Scott Martin look at the achievements of Susan Lunte and James Landers.